Social support, work motivation and work commitment of library personnel in selected private university libraries in south-west, Nigeria - Pius Olatunji, Olaojo; John Adeboye, Oyeboade (Qualitative and Quantitative Methods in Libraries, 2017)
The study was designed to investigate social support and work motivation as factors affecting work commitment of library personnel in private universities in South-West, Nigeria. Descriptive research design of the correlation type was adopted. Structured questionnaire was used to collect the data. Simple frequency count and percentage distribution, mean, standard deviation, ANOVA and correlation matrix table was used for the data analysis using Statistical Package for social sciences (SPSS). The findings of this study revealed that respondents have moderate work commitment in their various libraries. The findings revealed that there is significant positive relationship between: social support and work commitment of the library personnel (r = .111*; p < 0.05), work motivation and work commitment of the library personnel (r = .032*; df = 205; p < 0.05). Hence, the main factors that hinder work commitment of the library personnel include: insensitivity to library staff welfare, inability to acquire “state of the art” working equipment, poor funding of the library, among others.